Depth sensing-induced inelastic deformation at heterogeneous polymer surface. (26th June 2015) - Dai, L.; Sorkin, V.; Zhang, Y.W.
Abstract: Depth-sensing devices such as atomic force microscope have been widely used to characterize the morphology, nanostructure, surface composition and local materials properties of heterogeneous polymers. Such measurements are based upon a fundamental hypothesis that the deformation of polymer is elastic, that is, there is no tip-induced surface inelastic alteration or damage. Using molecular dynamics simulations, we show that the inelastic alteration at heterogeneous polymer surfaces induced by the sensing tip is intrinsic and unavoidable. Such tip-induced alteration arises from the differences in Van Der Waals interactions between different atomic species in the polymer and in the sensing tip, leading to atomic shuffling and re-shuffling, which cause inelastic alteration in both molecular structures and mechanical properties at and near the polymer surface. The present work highlights the need to reinterpret the data obtained from depth-sensing testing by considering this intrinsic inelastic deformation occurring at and near heterogeneous polymer surfaces. Graphical abstract: Highlights: Depth-sensing devices have been widely used to characterize the structure and properties of heterogeneous polymers. Atomic shuffling induced by van der Waals interactions is found to be intrinsic and unavoidable. The inelastic deformation renders the current depth-sensing interpretation model based on the elasticity theory invalid.